Penis w powieściach Szczepana Twardocha - Potkański, Jan (Przestrzenie Teorii, 2025)
The article discusses the penis motif in Szczepan Twardoch’s work, situating the issue in the broad context of contemporary culture and literature, as well as offering a theoretical interpretation inspired by psychoanalysis.